STUDI KINETIKA PRODUKSI BIOSURFAKTAN Bacillus subtilis 3KP PADA SUBSTRAT MOLASE - Ni’matuzahroh; Nur Hidayatul Alami; A. Faiz Khudlari T.; Fatimah; Tri Nurhariyati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Bacillus subtilis 3KP was a bacteria that can produce biosurfactant, when it was grown on a molasses substrate. This research was aimed to know the kinetic type of biosurfactant production, so it can be known the efficiency of molasses and the optimal culture condition to produce biosurfactant. B. subtilis 3KP was grown on mineral salt medium that had been already added with various molasses concentrations (1, 2, 3, and 4 g/l). The culture was incubated until 7 days on a shaker at 27° C and 120 rpm. The measurement of bacterial growth (CFU/ml), pH culture changing, and biosurfactant production which was indicated from emulsification activity and crude biosurfactant weight was determined at various incubation periods (0, 1, 2, 3, 4, 5, 6 and 7 days). Emulsifier activity (E1h) was measured by adding 1 ml of kerosene to 1 ml of biosurfactant supernatant. The measurement was made after 1 hour. The E1h index was given as percentage of height of emulsified layer (cm) divided by total height of the liquid column (cm). Crude biosurfactant was got from ammonium sulfate precipitation, then was dried and was determined in (g/l culture). The data of growth and biosurfactant production were analysed descriptively to know differentiation of biosurfactant production type of B. subtilis 3 KP in that different treatment. The examination of kinetics parameters such as product yield (Yp/x) and specific rate of culture (μ) were taken into account to evaluate a high efficient production process. The results of this research indicated that biosurfactant of B. subtilis 3KP was begun produced at exponential phase and was optimal at the end of exponential phase (production under growth-limiting conditions). Molasses concentration of 3% and 4 days incubation gave an optimal biosurfactant production, so it can be became the exact combination alternative to scale up biosurfactant of B. subtilis 3KP.